Faktor-faktor Pertumbuhan PT Bank Muamalat Cabang Kalimalang Bekasi Ditinjau dari Strategi Model Balanced Scorecard - Rizki Sartika; Nur S. Buchori (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2012)
This study aims to determine the growth factors PT. BMI Branch of Kalimalang-Bekasi model strategy in terms of the Balanced Scorecard. The method used is descriptive method with naturalistic qualitative data collection techniques, namely: interviews, observation, documentation and triangulation to be submitted to the HRD, Head. Operations and customers and several employees of PT. BMI Branch of Kalimalang-Bekasi. The study concluded that: Based on the Financial Perspective, the efficiency is demonstrated through BOPO still looks unstable because it has occurred in a higher efficiency than the year before and after the year 2009 which reached 80,94% BOPO shown performance measurements that are less effective efficiency even in the year 2010 has shown that effective and efficient measurement. Customer perspective shows that the measurement of customer growth appears to be ineffective. Measurement and control showed drastically reduced customer BMI Kalimalang Branch, among others: for customers saving as much as 20.634 (17.62%), deposits as many as 92 clients (11.68%), and the Giro as many as 1878 customers (58.63%). The condition was probably caused by internal factors in terms of services closely related to the level of customer satisfaction or can also be caused by external factors in this case is competitor other Islamic Banks. So it can be said is still low customer loyalty to the bank. Internal Business Processes perspective and learning and growth perspective is growth in a reasonable and very good. The results of this study encourage PT. BMI Branch of Kalimalang to better maintain its efficiency and maintain the loyalty of existing customers.